Strategi Komunikasi Menumbuhkembangkan Kecintaan Anak Sekolah Dasar Terhadap Ragam Hias Buleleng - suryawan suryawan (UHN IGB Sugriwa Denpasar, 2023)
This study aims to identify and implement effective communication strategies in developing elementary school children's love for Buleleng ornaments. Buleleng ornaments are part of a rich and unique local cultural heritage, but are often overlooked by the younger generation. Through a qualitative approach and action research methods, this research involves the active participation of children in learning and exploration activities related to Buleleng ornaments. The steps taken in this study included conveying interesting information about Buleleng ornaments, visiting exhibitions or creative centers, creative activities using Buleleng decorations, collaboration with local communities, performances or exhibitions of works, integration into the curriculum, and community empowerment. Evaluation is carried out through participatory observation, interviews, questionnaires, knowledge tests, evaluation of works and performances, and feedback from stakeholders. The results of this study indicate that the steps taken as a whole are effective in developing elementary school children's love for Buleleng ornaments. Children showed high interest, active involvement, and increased their knowledge of Buleleng ornaments. They also produce works of art and performances that reflect their understanding and application of Buleleng ornaments. This research makes an important contribution in understanding how effective communication strategies can be used to develop elementary school children's love for local cultural heritage such as Buleleng ornaments. The implication of this research is the importance of integrating local cultural activities into the curriculum and involving the community in the learning process. In addition, this research also highlights the importance of creative and interesting approaches in conveying information about cultural heritage to children.